A Comparative Study of Longitudinal Toxicities of Cytotoxic Drugs, Molecularly Targeted Agents, Immunomodulatory Drugs, and Cancer Vaccines. Issue 4 (29th April 2019) - Hirakawa, Akihiro; Sudo, Kazuki; Yonemori, Kan; Sadachi, Ryo; Kinoshita, Fumie; Kobayashi, Yumiko; Okuma, Hitomi S.; Kawachi, Asuka; Tamura, Kenji; Fujiwara, Yasuhiro; Rubinstein, Larry; Takebe, Naoko
Abstract : Little is known about the toxicity of various therapeutics for cancer over time because randomized controlled clinical trials that compare several treatments are limited. In this study, we focused on the toxicities most frequently discussed, which are investigations (lab abnormalities), gastrointestinal disorders, skin and subcutaneous tissue disorders, and cardiac disorders, and compared their longitudinal toxicity data among four types of cancer therapeutics. In total, 28, 235 patients who were enrolled into 772 early‐phase trials to evaluate the monotherapies of cytotoxic drugs, molecularly targeted agents, immunomodulatory drugs, or cancer vaccines were evaluated. For each toxicity, we compared their grade prevalence, mean grade at each cycle, and time to toxicity occurrence and identified the potential underlying similarities and differences of longitudinal toxicities among the four cancer treatment types. Our results will further help in understanding the profile of cancer therapeutic toxicities and their impact on oncology treatment in practice.